The materiality of sound in chant manuscripts in the West - De Luca, Elsa; Moody, Ivan 1964-2024; Goudesenne, Jean-François 1965- (Brepols, 2023)
A new, innovative and interdisciplinary collection of essays by leading scholars in two volumes dealing with chant transmission and manuscripts in both East and West, this publication is the first of its kind in the wide scope, both geographical and historical, of the variety of traditions it covers.
Keywords: Geschichte 800-1500; Gregorianischer Gesang; Paläographie; Neumenschrift; Materialität; Musikhandschrift; Liturgie; Historische Musikpraxis; Europa; Aufsatzsammlung